The efficacy and tolerability of auto-stimulation-VNS in children with Lennox-Gastaut syndrome. (March 2021) - Abdelmoity, Sherouk A.; Abdelmoity, Ayman A.; Riordan, Sean M.; Kaufman, Christian; Le Pichon, Jean-Baptiste; Abdelmoity, Ahmed
Highlights: The auto-stimulation VNS models are safe and effective in children with Lennox-Gastaut syndrome. 65 % of children achieved greater than 50 % reduction in seizures frequency at 24 months and 17 % were seizure free. Compared to the traditional VNS, the auto-stimulation VNS provide additional benefits in seizure reduction and quality of life. Abstract: Objective: Lennox-Gastaut syndrome (LGS) is a severe drug-resistant epilepsy (DRE) of childhood. The Vagus Nerve Stimulator (VNS) is established as a safe and effective treatment for DRE. This study assesses efficacy and tolerability of the auto-stimulation VNS models in pediatric patients with LGS. Methods: This is a retrospective chart review of a cohort of pediatric patients (Age 1–18 years old) with LGS implanted with an auto-stimulation VNS model at a single level four pediatric epilepsy center. Patient responder's rate was measured as seizure reduction over baseline and improvements in five quality-of-life measures as reported by the patients and families. Efficacy and tolerability were assessed at 1, 3, 6, 12, 18 and 24 months compared to baseline. Results: This cohort includes 71 consecutive children with Lennox-Gastaut syndrome who underwent implantation with one of two models of the auto-stimulation VNS. The average age of the children at implantation was 20.82 months. Of those patients, 55 % of patients achieved greater than 50 % seizure reduction at six months, 67.7 % at 12 months, and 65 % at 24 months. At 12 months 11 % of the patients were completely seizure free and at 24 months 17 % were seizure free. By 24 months post implantation most of the patient families reported at least a 50 % improvement rate in one or more of the quality-of-life measures. The most commonly reported adverse events were dysphonia, paresthesia, and shortness of breath, all of which were tolerated and subsided by 24 months. Significance: This study provides evidence that VNS models with the auto-stimulation paradigm based on detection of tachycardia are well tolerated and effective in a pediatric population with LGS. Furthermore, this study shows that for this population, the auto-stimulation models of the VNS may provide additional benefits over the earlier VNS versions.